(untitled) (مجلة دراسات إقلیمیة, 2026)
Research Idea: This research examines Iran’s policy toward Eritrea during 2005–2025 and explores how Iran has sought to expand its presence and influence in the Horn of Africa by exploiting Eritrea’s strategic location on the Red Sea. Objective: The research aims to identify the political, economic, military, and cultural tools employed by Iran to achieve its objectives in Eritrea and to assess the impact of competing actors, particularly Israel, Turkey, and Saudi Arabia, on this policy. Methodology: The research adopts a descriptive-analytical approach by describing Iran–Eritrea relations and analyzing their motivations and mechanisms. Results: The findings indicate that Iran succeeded in establishing a strategic presence in Eritrea by exploiting regional power vacuums and geopolitical opportunities. However, competing actors exerted significant pressure that constrained the expansion of Iranian influence. Conclusion: The research concludes that Iran’s policy toward Eritrea during 2005–2025 was driven by the country’s geostrategic position on the Red Sea and relied on diplomatic, economic, security, and cultural tools to build strategic influence. Despite Iran’s success in developing a multidimensional presence, its influence was constrained by competing actors, particularly Israel, Turkey, and Saudi Arabia. Iranian policy demonstrated flexibility and adaptability within a complex regional environment, while competition in the Horn of Africa remains open to multiple scenarios.